One thing at a time, one thing after another : an inquiry into time in the domestic sphere. - Alwyn, Jeni (Curtin University, 2001)
This is a thesis about time. It is sited in Perth, Western Australia. Like other Australian states, Western Australia has a modern market system economy and enjoys, comparative to other countries with a market system economy, well developed social welfare and public education systems. The thesis shows how a set of fifteen people from Perth, Western Australia, who had all experienced a change in their domestic arrangements, understood time in the domestic sphere. Drawing upon their representations and constructions of their lives, and focusing on the concept of caring, this work demonstrates how temporal concepts can be utilised to control and limit choices these people have made in their lives.The evidence, collected through a series of open-ended and on-going discussions, is synthesized with theory, particularly the work of Barbara Adam. To Adam, an understanding of time involves appreciating the complexity of time. To gain such an understanding requires a research paradigm that allows this. Such an understanding requires stepping outside Cartesian dualistic thinking, including entrenched notions such as gendered time, and, an appreciation that differing temporal concepts exist and are utilised as mechanisms of control.